(untitled) (Indian Journal of Chemistry (IJC), 2023)
New phosphonate functionalized naphthalenediimides (NDI-1 and NDI-2) have been synthesized and evaluated as potential drug candidates to treat the skin malignancy. The aforementioned candidates have resulted in an induced apoptosis pathway of cytotoxicity, at concentrations lower than 4 µM, in human skin melanoma cells, and elicited a stronger apoptotic response in cells. Regulation of the Bcl2, Caspases, Bak1, Bax protein in NDI-induced apoptosis in cells has been analyzed by real time PCR, and the cell viability and apoptosis determined by flow cytometry. The obtained results indicate that NDI-induced apoptosis by regulation of Bcl2 and Bak1 occurs in human skin melanoma cells (SKMEL-2).